Legionella Contamination in Water Environment - Bonetta, Silvia; Bonetta, Sara (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Legionella spp. are ubiquitous microorganisms that are widely distributed in aquatic environments. Water systems of large buildings, such as hospitals, hotels, and rental units are often contaminated by legionellae and various parameters such as physical, chemical, and microbial building water system characteristics can influence Legionella occurrence. A range of physical and chemical disinfection methods have been proposed to control Legionella contamination; however, to date, the most effective procedures have not been defined. There is a need to survey legionellae in water systems to prevent legionellosis. Although the assessment of L. pneumophila in water is typically performed by culture isolation on selective media, it has several limits. For this reason, alternative tools for rapid, sensitive, and specific detection of Legionella in water samples have been proposed. In order to increase knowledge on different aspects of Legionella contamination in the water environment, this book gathers research studies related to the occurrence of Legionella in water systems of different environments; the role of different factors that can influence the Legionella contamination, as well as the advantages and disadvantages of different methodological approaches.